Mechanism of hot spots formation in pentaerythritol tetranitrate under pulsed laser irradiation; IOP Conference Series: Materials Science and Engineering; Vol. 510 : High Technology: Research and Applications (HTRA-2018) - Oleshko V. I. Vladimir Ivanovich; Tsipilev V. P. Vladimir Papilovich; Zarko V. E.; Yakovlev A. N. Aleksey Nikolaevich; Mazur M. A. Marina Aleksandrovna (2019, 2019)
Title screen